HUBUNGAN ANTARA HARDINESS DENGAN PSYCHOLOGICAL WELL-BEING PADA ANAK SULUNG PEREMPUAN - Ratu Aqilah, Bilqies; Jaro’ah, Siti (Lafadz Jaya Publisher, 2026)
This study explores how the demands and expectations experienced by firstborn daughters within a collectivistic cultural context are associated with psychological well-being, with an emphasis on hardiness as an internal protective factor. The purpose of this study was to determine the relationship between hardiness and psychological well-being among firstborn daughters in early adulthood in Surabaya. This study employed a quantitative approach with a correlational design. Participants consisted of 115 firstborn women aged 18–25 years selected using a convenience sampling technique. Data were collected using the Hardiness Scale adapted for early adulthood and the Indonesian adaptation of Ryff’s Psychological Well-Being Scale. Data analysis included descriptive statistics, normality and linearity tests, and Pearson Product Moment correlation analysis. The results showed a strong and significant positive relationship between hardiness and psychological well-being (r = 0.807; p < 0.01). These findings indicate that individuals with higher levels of resilience, commitment, control, and readiness to face challenges tend to have better psychological well-being. The magnitude of the relationship also suggests that hardiness is an important psychological factor in supporting psychological well-being among firstborn daughters in early adulthood. These findings imply that strengthening hardiness may serve as an important strategy for enhancing psychological well-being among firstborn daughters who face complex social and family role demands. Future studies are recommended to consider other factors that may influence psychological well-being in similar populations.